Green Synthesized Silver Nanoparticles as Potent Antifungal Agent against Aspergillus terreus Thom. (27th August 2021) - Anum, Faiza; Jabeen, Khajista; Javad, Sumera; Iqbal, Sumera; Tahir, Arifa; Javed, Zeeshan; Cruz-Martins, Natália; Ayatollahi, Seyed Abdulmajid; Sharifi-Rad, Javad; Alshehri, Mohammed M.; Cho, William C.
Abstract : Medicinal plants are composed of a rich pool of biomolecules and have been increasingly recognized for their antimicrobial properties; however, increasing concerns have been put on the bioavailability features. Thus, this study is aimed at exploring the synthesis and characterization of silver nanoparticles synthesized by Chenopodium album L. leaf extract and assessing the antifungal activity against Aspergillus terreus Thom. Plant extract was prepared in methanol to synthetize silver nanoparticles, which were then characterized by Scanning Electron Microscopy (SEM), UV-Visible spectroscopy, and particle size analysis. UV-Visible analysis indicated maximum absorption at 378 nm, and an average particle size was observed as 25.6 nm. Oval to hexagonal shape was observed by SEM. Antifungal activity of silver nanoparticles (1, 1.5, 2, 2.5, 3, and 3.5%) was addressed against A. terreus biomass. At 3.5%, silver nanoparticles revealed to be highly effective, leading to 92% retardation in fungus growth. In next phase, various organic fractions, viz., chloroform, n -butanol, n -hexane, and ethyl acetate, were obtained from plant methanol extract, and the corresponding silver nanoparticles were prepared. These fractions were also assessed for antifungal activity, and n -hexane fraction led to 64% inhibition in A. terreus biomass. Following gas chromatography-mass spectrometry (GC-MS), 18 compounds were identified, namely, 1, 3-cyclopentadiene-5-(1 methylethylidene and o-xylene), ethyl benzene, octadecane, nonane, decane, 2-methylheptane, n -hexadecane, 2-methylheptane, and eicosane, along with carbonyl compounds (4, 4-dimethyl-3-hexanone) and phenols, like stearic acid, propionic acid hydrazide, and 2, 4-di-T-butylphenol. These findings proved that C. album silver nanoparticles are highly effective against A. terreus .